Country Partnership Framework for Republic of Guinea Bissau for the Period FY18-FY21 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
This World Bank Group (WBG) Guinea-Bissau country partnership framework (CPF) will be the first full country strategy since 1997. The development of the CPF has benefited from the findings of the 2016 systematic country diagnostic (SCD) and the 2015 fragility assessment, and addresses the main lessons learned from the completion and learning review (CLR) at annex 2. It also reflects feedback from consultations with the government, private sector, civil society, and development partners. This CPF supports the national development plan, Terra Ranka (fresh start), which was developed by the government elected in 2014. The CPF presents a selective and flexible WBG program. The focus areas of the CPF program will be on increased access to quality basic services and expanded economic opportunities and enhanced resilience to shocks.